THE ROLE OF PEDAGOGY IN EFFECTIVE EDUCATION - Ibrahimov, Shertoy; Rahmatova, Laziza (Science technology&Digital finance, 2023)
This article provides information on how pedagogical processes are carried out in the current modern period, pedagogical approaches and the role of pedagogy in an effective educational system.